It The participatory management of public services oriented to national development - Cavani Rios, José Eduardo (2024)
The management of public services is a normative attribution of state entities, which, interpreted in a strict sense, ignores citizen intervention in all its phases, despite being the person the central axis of public management modernization policies and the final recipient of the first objective of the Strategic Plan for National Development by 2050. From a qualitative methodological approach, the hermeneutic interpretation of the single case study presents the distance established between public policy and technical standards that regulate the quality of state production of services public, and the way in which the strategic planning of National Development intervenes as the most successful mechanism to accelerate the closing of this gap. The conclusion of the study is the assimilation of the modernization policy to the technical quality standards of the public sector.